Antioxidant Effect of Thyme (Thymus vulgaris L.) and Oregano (Origanum vulgare L.) Extracts in Soybean Oil Under Thermoxidation. Issue 6 (23rd September 2014) - Jorge, Neuza; Veronezi, Carolina Médici; Del Ré, Patricia Vieira
Abstract: The rancidity of vegetable oils is considered one problem in the food industry, thus, are added antioxidants in food. The objective of this study was to investigate the antioxidant effect of oregano and thyme extracts in soybean oil under thermoxidation. Soybean oil containing 3, 000 mg/kg of oregano and thyme oleoresins and the mixture of both, as well as soybean oil containing tert‐butylhydroquinone (TBHQ; 50 mg/kg) and soybean oil free of were subjected to thermoxidation. Then, the physicochemical properties and fatty acid profile were evaluated. Oregano and thyme oleoresins applied separately presented a higher protective effect, inhibiting a greater formation of polar compounds than the antioxidant TBHQ, indicating that the addition of 3, 000 mg/kg has ensured a better oxidative protection than the synthetic antioxidant. The increase in the concentration of oleoresins by mixing thyme and oregano extracts has given a higher protective effect. Practical Applications: Oxidation is a problem encountered in the food industry, whereas food‐based oils are susceptible to oxidative degradation. To avoid this, the industry uses antioxidants that can be natural or synthetic. The use of natural antioxidants has increased because of the high demand for healthful food products and proven toxicity of some synthetic antioxidants. Many spices and herbs, such as those belonging to the family Lamiaceae, show antioxidant activity highlighting the oregano and thyme. Thus, being rich in compounds with high antioxidant activity, these extracts can be used to replace synthetic antioxidants used in vegetable oils.